(untitled) (Advancements in Homeopathic Research, 2024)
In their previous five publications Gupta et. al. demonstrated that patients of chronic kidney disease (CKD) and acute renal failure (ARF) can be successfully managed by homoeopathic medicines. This sixth case series put forth herewith is on successful management of CKD patients by maintaining their serum creatinine level and eGFR within a reasonable range, delaying further deterioration and improving their quality of life for a considerable period of time without haemodialysis. The first case in this series is of 63-year old normotensive, non-diabetic female suffering from CKD having single kidney after donating a kidney to her son having CKD. Her S. Creatinine level is maintained for more than 5 years and she is still under treatment. The second case is of a 63-year old hypertensive, nondiabetic female. Her S. creatinine and eGFR was maintained for more than 3 years. In third female patient aged 75-year, who was hypertensive and non-diabetic, S. creatinine and eGFR was maintained for about 3 years.